2020
DOI: 10.4055/cios19069
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry of Nonarthritic Asian Knees: Is It Time for a Race-Specific Knee Implant?

Abstract: The morphology of the knee joint has been proven to vary considerably amongst the various ethnic groups, genders, and morphotype of the patients. Having a normative data for a particular population subset is important as it helps to design the knee joint prosthesis that will have the best fit and size for the knees. 1) Suboptimal sizing and placement leads to various issues like patellar maltracking, persistent pain, early loosening, loss of bone stock, and increase in propensity of periprosthetic fractures. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
(19 reference statements)
8
19
0
Order By: Relevance
“…We found that male patella was significantly larger of all measurement of patella except patellar cartilage which is consistent with other literatures [ [11] , [13] , [14] , [15] ]. Hence, this will need a consideration during a patellar resurfacing or replacement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that male patella was significantly larger of all measurement of patella except patellar cartilage which is consistent with other literatures [ [11] , [13] , [14] , [15] ]. Hence, this will need a consideration during a patellar resurfacing or replacement.…”
Section: Discussionsupporting
confidence: 93%
“…The aim was to aid surgeons achieving the anatomic native patella size during patellar resurfacing or replacement in TKA. Several literatures ( Table 3 ) found female Asian patellae were significantly smaller compared to Caucasian's [ 1 , 12 , 13 ]. However, our finding showed similar dimension between Asian and Caucasian patellae.…”
Section: Discussionmentioning
confidence: 99%
“…We found that male patella was signi cantly larger of all measurement of patella except patellar cartilage which is consistent with other literatures [12][13][14]. Hence, this will need a consideration during a patellar resurfacing or replacement.…”
Section: Discussionsupporting
confidence: 90%
“…Several literatures (Table 3) found female Asian patellae were signi cantly smaller compared to Caucasian's. [1,11,12]. However, our nding showed similar dimension between Asian and Caucasian patellae.…”
Section: Discussionsupporting
confidence: 57%
“…Clinical comparison of axial rotational reference lines is difficult. First, each patient has unique knee anthropometry [10][11][12][13]. Secondly, each patient has a unique degenerative history creating their knee deformity.…”
Section: Introductionmentioning
confidence: 99%